Covid 19 and the move to online teaching: impact on perceptions of belonging in staff and students in a UK widening participation university (Journal of Applied Learning and Teaching, 2020)
Belonging within higher education benefits students, staff and institutions. The Covid 19 pandemic necessitated campus closures at short notice, with teaching and assessment moving online. Understanding the impact of this upon belonging from both staff and student perspectives, and exploring whether demographic or study characteristics have an impact, is needed to inform future educational provision. A bespoke questionnaire collecting quantitative and qualitative information was administered online to staff and students at a UK university with a strong widening participation focus. A total of 208 students and 71 academic staff responded. Staff were significantly more likely than students to recognise belonging as important. Lockdown reduced feelings of belonging in both groups, and physical presence on campus was highlighted as important by both. Despite considerable diversity, student responses showed a high degree of homogeneity. Although advantages to future online teaching were identified by both staff and students, almost half of students disagreed that they would learn better if future teaching remained online. A greater proportion of staff identified teacher online presence and facilitating active learning as essential in helping students to belong, but what students consider essential in online teaching to enhance belonging is less clear from this data.